Radial Artery Versus Saphenous Vein as Third Conduit in Coronary Artery Bypass Graft Surgery for Multivessel Coronary Artery Disease: a Ten-Year Literature Review - Maestri, Francesco; Formica, Francesco; Gallingani, Alan; Gripshi, Florida; Nicolini, Francesco (Acta Biomedica Atenei Parmensis, 2022)
Coronary artery bypass grafting is the gold standard strategy for obtaining complete coronary revascularization in patients with multivessel coronary artery disease. The recent AHA and EACTS guidelines on myocardial revascularization recommend total arterial revascularization, especially in younger patients, whenever possible. However, the use of saphenous vein grafts in association with single or bilateral internal thoracic artery (SITA, BITA) instead of arterial grafts (radial arteries, right gastroepiploic artery and inferior epigastric artery) is widespread. We analyzed literature from the last ten years (January 2010 to December 2020) looking for evidence in favour of the use of a radial artery compared to a saphenous vein in association with BITA. We identified nine studies (4 Systematic Reviews and Meta-analyses and 6 large cohort observational studies with propensity score-matching) that compared arterial with saphenous grafts as third conduit. The main finding of the review is the higher rate of freedom from any cardiac adverse event in the population which reached Total Arterial myocardial Revascularization (TAR). A probable reason for the limited application of TAR as a strategy is the shortage of Randomized Controlled Trials (RCTs).